Bargaining frictions and hours worked - Stéphane Auray; Samuel Danthine (Institute for the Study of Labor (IZA), 2005)
A matching model with labor/leisure choice and bargaining frictions is used to explain (i) differences in GDP per hour and GDP per capita, (ii) differences in employment, (iii) differences in the proportion of part-time work across countries. The model predicts that the higher the level of rigidity in wages and hours the lower are GDP per capita, employment, part-time work and hours worked, but the higher is GDP per hours worked. In addition, it predicts that a country with a high level of rigidity in wages and hours and a high level of income taxation has higher GDP per hour and lower GDP per capita than a country with less rigidity and a lower level of taxation. This is due mostly to a lower level of employment. In contrast, a country with low levels of rigidity in hour and in wage setting but with a higher level of income taxation has a lower GDP per capita and a higher GDP per hour than the economy with low rigidity and low taxation, because while the level of employment is similar in both economies, the share of part-time work is larger.
Keywords: E24; J22; J30; J41; J50; J64; 330; model of search and matching; bargaining frictions; economic performance; labor market institutions; part-time jobs; labor market rigidities